Negotiating Religious Moderation: Qur'anic Interpretation And The Construction Of Wasatiyyah Discourse In Indonesia - Syamsuni, Syamsuni (Interdisciplinary Explorations in Research Journal, 2026)
This article examines the construction and negotiation of wasatiyyah (Islamic moderation) discourse in Indonesia through Qur'anic interpretation as a complex socio-religious phenomenon. Drawing on discourse analysis and critical examination of contemporary tafsir literature, this study demonstrates that wasatiyyah is not a static theological concept but a contested discursive space negotiated among state institutions, Islamic scholars, civil society organizations, and digital platforms. The analysis reveals that while wasatiyyah discourse is promoted as an authentic Islamic principle grounded in Qur'anic teachings particularly the concept of "ummatan wasatan" in Surah Al-Baqarah verse 143 its actual implementation reflects diverse, sometimes contradictory interpretations shaped by socio-political contexts. The study argues that understanding wasatiyyah requires attention to how different actors strategically employ Qur'anic exegesis to construct narratives of religious moderation aligned with their institutional interests. This article contributes to Islamic studies and religious discourse analysis by illuminating the power dynamics embedded in the production of religious knowledge and the negotiation of moderate Islam in pluralistic Indonesia.